IMAGERY DEALING WITH CHOICE OF LIFE IN ROBERT FROSTâ€™S â€œTHE ROAD NOT TAKENâ€ - Yuda Sanjaya; Arielia Yustisiana; Eko Budi Setiawan (Universitas Katolik Widya Mandala Surabaya, 2017)
The research aims to discuss the imagery dealing with the choice of life in RobertFrostâ€™s â€œThe Road not Takenâ€. The research has three purposes: (1) to describethe kinds of imagery in the poem, (2) to describe the choices of life in the poemâ€,and (3) to figure out how the imagery deals with the choice of life in the poem.The theories used in the research are the theory of imagery and its kinds andtheory of symbol. Next, formalistic and structural approaches are applied toanalyse the data. Further, descriptive method and library research are used tofacilitate the analysis and seek for the data in the research. Visual, organic andkinaesthetic imageries are imageries that reflect the choice of life in the poem. Inthe poem, the speaker is taking a very different way of life but sad and tragic thathe believes that it will make him stronger in life. Life is a choice. Whatever thechoice he takes, he will be ready to face obstacles that come and block him. Hissoul is really brave. He believes that to experience a beautiful life, he must passthe hardest things in his life. What burdens him today will strengthen himsomeday.